Kelimpahan Ikan Chaetodontidae Dan Pomacentridae Di Ekosistem Terumbu Karang, Tanjung Labu - Ferizal, Jemi; Sudarmo, Agnes Puspitasari; Susanto, Adi (Journal of Tropical Marine Science, 2024)
Tanjung Labu waters have a coral reef ecosystem and are rich in a variety of biota such as the Pomacentridae and Chaetodotidae families. This family is an indicator of the health of coral reefs and plays a role in maintaining ecosystem balance. The aim of the research is to calculate the abundance of the Chaetodontidae and Pomacentridae families and analyze the relationship between the abundance of Chaetodontidae and Pomacentridae fish and habitat characteristics in coral reef ecosystems. The research was carried out in March 2024 in the waters of Tanjung Labu. The method used is UPT (Underwater Photo Transect) for coral reefs and UVC (Underwater Visual Census) for coral reef fish and the PAST 4.03 application to determine the relationship. The research results showed that the average live coral cover was 51.15%, and the abundance of the Chaetodontidae and Pomacentridae families was 1/m2. The number of individuals and species of the Chaetodontidae family is 37 individuals and 3 species, while the Pomacentridae family is 386 individuals and 20 species. The Chaetodontiadae family relationship is positively correlated with basic substrate cover components such as abiotic and other fauna, as well as environmental parameters such as brightness and current speed, but is negatively correlated with live coral and the type of coral reef life form, while the Pomacentridae family relationship is positively correlated with the closure component. basic substrates such as coral reef life form and dead coral, as well as environmental parameters such as water depth.